Just doing it: theorising integrated marketing communications (IMC) practices. (10th April 2017) - Ots, Mart; Nyilasy, Gergely
Abstract : Purpose: This paper aims to elaborate on the concept of "integrated marketing communication (IMC) practice" and provide an empirical exposition of how integration is enacted in the lifeworlds of marketing practitioners, drawing from the "practice turn" in management studies. Although IMC is a well-known conceptual idea in academia, there is insufficient theorisation of what it means "to do" IMC. Despite broad acceptance for IMC, there has been scant application of available organisational and sociological theories to illuminate actual IMC practices in the field. Design/methodology/approach: The paper introduces practice theory as a lens through which to study and analyse IMC practices. Using qualitative coding and interpretative analysis, the framework was operationalised and applied to a two-year organisational ethnography encompassing IMC planning activities in at a leading Swedish retailer. Findings: Findings demonstrate how practitioners develop explicit and implicit strategies to enact strategic integration. The study conceptualises IMC as a set of interrelated practices, or routinised behaviours, which are repeated and organised by some social or formal rules and conventions. In the ethnographic context of the study, "IMC as practice" is exhibited in the forms of routines, material set-ups, rules and procedures, cultural templates and teleoaffective structures. Originality/value: The paper proposes a novel set of theoretical and methodological tools that can be used to understand how IMC lives as a set of practices inside organisations. It specifically conceptualises the link between mental and objectified, materialised and routinised activities that has previously been escaping the sphere of theorisation. By creating language and tools to capture hitherto unmodellable phenomena, the paper opens many new avenues for future research.